The determinants of mobile banking adoption in Somalia - Mouse, Khalif Hussein (2019)
This study focuses on mobile banking adoption in Somalia, and how technological advancement has changed the traditional banking system. Also, it highlights the concerns arising from the adoption of M-banking such as trust and perceived risk. Since there are no much prominent studies in this area, the cu1Tent study will contribute to the improvement of M-banking in Somalia. The objective of this study is to examine the influence of perceived risk, trust and M-banking adoption. This study also examined the relationship between M-banking adoption and its predicators of effort expectancy, performance expectancy, facilitating conditions and social influence with the underpinning theory of the Unified Theory of Acceptance and Use of Technology. Quantitative method is used in this study by employing online questionnaire survey for data collection, and statistical tools of Statistical Package for Social Science (SPSS) for data analysis. The result suggests that mobile banking adoption is significantly associated with effort expectancy, performance expectancy, trust and perceived risk. However, the relationships between social influence and facilitating conditions towards mobile banking adoption are found to be not significant. The findings have both theoretical and practical significance. In terms of the practical aspect, the research findings of this study will provide banking institutions and mobile banking practitioners with useful information in formulating strategies that can enhance the adoption of mobile banking services. Theoretically, the study findings contribute to the body of literature in the field of mobile banking adoption